Pengaruh Penambahan Abu Gergaji Kayu pada Tanah Fat Clay Ditinjau Dari Indeks Properties Tanah dan UCST (Unconfined Compressive Strength Test) - Rizki Diana Putri S; Dila Oktarise Dwina; Yulia Morsa Said (Jurnal Talenta Sipil, 2023)
The soil is the base layer of the construction that must have good carrying capacity. To find out the magnitude of the carrying capacity of the soil, one of them is using UCST (Unconfined Compressive Strength Test) testing. This study was conducted by taking soil samples in Olak Kemang Seberang Jambi City which is classified as fat clay soil. The purpose of this study was to see the effect of addition saw ash wood towards soil properties index values and UCST (Unconfined Compressive Test). The percentage of addition of saw ash wood used is 8%, 10%, 12%, and 14%. Based on the test results, changes in the value of the soil properties index experienced a peak at a percentage of 14%  for each test of moisture content, specific gravity, and atterberg. Based on the results of the UCST test conducted, the peak of the increase in the highest soil carrying capacity value at a percentage of 14% was 4.02 kg / cm2, an increase from the original soil UCST value of 2.15 kg / cm2.